ANALISIS HIDROLOGI DAN HIDROLIKA PERENCANAAN KOLAM RETENSI JALAN MARELAN 4 - Hutapea, Timbul Parningotan; Wijaya, Kinanti; Yuzni, Siti Zulfa (Universitas Negeri Medan, 2025)
Flooding problems often become a major issue, especially in urban areas. Floods generally occur because the volume of water that falls cannot be accommodated in the water-receiving body. Changes in land use to residential areas or other activity centers have an impact on reducing the absorption capacity of the soil surface so that the soil surface becomes saturated and results in water runoff. The purpose of this research was to determine hydrological analysis and hydraulic analysis to become a reference in planning retention ponds in Jalan Marelan IV, Medan Marelan District, Medan City. The research method uses field observation (observation) and secondary and primary data collection. Calculation analysis uses various formulas to calculate hydrological analysis and hydraulic analysis. The results are 1) Flood prevention in the Marelan IV area is focused on the 2 existing channels (inlet and outlet channels), 2) Channel capacity is calculated based on the hydrological data input above and produces cross-sectional dimensions according to the results of hydraulic analysis calculations, 3) Rainfall data used is data for the last 10 years (2013 – 2022) in the form of maximum daily rainfall data, 4) The flood discharge for 5 years was 7,030 m3/sec, while the Karmila ditch only had a discharge of 6,435 m3/sec, so the unaccommodated discharge was 0.615 and the discharge will be diverted to the retention pond. 5) The results of the retention pond planning show that the width is 74 meters, the length of the right side is 231 meters, the length of the left side is 233 meters, the depth is 1.5 meters, the inlet width is 2 meters, the inlet depth is 1.5 meters. The outlet width is 0.7 meters and the outlet depth is 0.5 meters, 6) Design of the Jalan Marelan IV Retention Pool, namely the pool area is 2,026 Ha, the pool depth is 2 meters, the effective height is 2 meters.